2013
DOI: 10.5702/massspectrometry.a0016
|View full text |Cite
|
Sign up to set email alerts
|

The pH Dependence of Product Ion Spectra Obtained from Precursor Ions with the Same Charge Number in ESI of Carbonic Anhydrase 2

Abstract: The effect of solvent conditions, including pH, on product ion spectra obtained from precursor ions produced by electrospray ionization (ESI) was examined. Bovine carbonic anhydrase 2 was used as a model protein and the product ions generated by collision induced dissociation of the whole protein were measured under several different solvent conditions (pH 5.0, 3.7, and 0.1% HCOOH (pH 2.6)/MeCN (1/1)). The product ion spectra from precursor ions with the same charge number, the observed m/z values and the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“… 22 ) From the product ion spectra obtained under several different solvent conditions, we showed that the folding states of the C-terminal region of the protein were influenced by the solvent. 23 , 24 ) However, the relationship between the folding states of CA2 ions and their molecular size have not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“… 22 ) From the product ion spectra obtained under several different solvent conditions, we showed that the folding states of the C-terminal region of the protein were influenced by the solvent. 23 , 24 ) However, the relationship between the folding states of CA2 ions and their molecular size have not yet been examined.…”
Section: Introductionmentioning
confidence: 99%